An experimental investigation of the yarn pull-out behavior of plain weave with leno and knitted insertions. Issue 21 (November 2019) - Yi, Zhou; Ali, Muhammad; Gong, Xiaozhou; Dai, Hanming; Zhongmin, Deng
Yarn–yarn sliding force plays a vital role in absorbing impact energy for plain fabrics. This paper reports the methods and results of an investigation on the mechanisms that enable higher yarn pull-out force of woven fabrics with the incorporation of lenos and knits. The experimental results suggested that the insertion of leno lines on plain weave gives an approximately 20% increase in junction rupture force over the original plain construction. With knitted structures inserted, the structure-modified fabrics showed a junction rupture force up to about 15 times higher than simple plain weave. It was even found that the yarns failed rather than pulled out in multiple yarn pull-out tests. This is because knitted structures tend to become self-locked and consequently restrict yarn displacement when subjected to external loading. This investigation reports a method to increase the frictional force between the warp and weft yarns based on textile technologies. It is expected that the results obtained could provide some useful information for the engineering design of flexible ballistic protection systems.